A contribution to the study of older granites in the Nigerian Precambrian with special reference to the Tegina granite - Truswell, J F; Truswell, John Francis (Department of Geological Sciences, 2017)
Rocks of the Older Granite suite occur throughout the Nigerian Precambrian. In part 1 of this thesis an example, the Tegina granite, is examined in detail. In part II the suite as a whole is described and discussed. The granite is an elongate mass covering an area of 49 square miles. Structural analysis indicates its vertical emplacement under internal pressure. The pressure was maintained during the formation of joints and secondary structures. Three petrological units are recognised in the granite. (1) The Main granite, a porphyritic biotite granite. Granodiorite and quartz-diorite in it represent local or marginal contamination. (2) Similar rocks are developed in the zone of banded foliation. In addition, there are remnant bands of granodiorite providing evidence that the 'granite' was formed as granodiorite subsequently 'granitised' with the formation of late phenocrysts of microcline microperthite. (3) The later biotite-muscovite microgranite at Karaya.